Systematic review of intervention programs to improve the level of knowledge, attitude, and practices towards work safety culture among office workers - Oluwaseun Odu, Josiah; Hamedon, Titi Rahmawati; Mahmud, Aidalina; Baharudin, Mohd Rafee (Universiti Putra Malaysia, 2023)
Introduction: Workplace safety culture (WSC) is crucial in providing a safe working environment. Workers need to be reminded regularly of its importance, and therefore effectively, work safety intervention programs need to be identified to be used for this purpose. The main objective is to identify workplace intervention programs to improve WSC among office workers. The specific goals are to determine the types of intervention (knowledge-based, attitudinal, and practices-based interventions), the theories used, and the effectiveness. Methods: Databases such as ProQuest, CINAHL, Medline, and ScienceDirect were used to perform literature searches with the keywords [“safety culture training” OR “safety culture education” OR “safety culture promotion”] AND [“office workers” OR “civil servant” OR “white-collar workers” OR “administrative officers” OR “clerical officer”]. The inclusion criteria set for the search process included research articles, publication between January 1, 2015, and September 10, 2020, which were research articles within five years and eight months of publication to the time of data extraction of this study. Availability of full-text articles, articles published in English, and only articles among office workers. Results: This review includes seven articles and the techniques used for these studies were knowledge, attitude, and practices towards WSC. Conclusion: As the number and scope of intervention of studies on WSC seem scarce, the nature of jobs nowadays and in the future seems to be more office-based; consequently, more of these studies are recommended among office workers.